Kamus sains dan teknologi - Mohd Amran Daud; Rohana Abdul Rahman; Emyliza Sharida Asari; Siti Afifah Samsuddin; Siti Haslina Subaker; Siti Nur Atiqah Amirudin; Syahidah Rasyiqah Abd Rashid; Siti Nur Atiqah Amirudin; Siti Afifah Samsuddin; Nurul Shaheza Zamri; Shamsul Firdaus Rizyan; Sharizul Razli Seth; et al. (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2017)
English-Malay and Malay-English dictionary of science and technology.
Malay and English.
Keywords: Science -- Dictionaries; Science -- Dictionaries -- Malay; Technology -- Dictionaries; Technology -- Dictionaries -- Malay